Analysis of the Existence of the Corruption Eradication Commission in Handling Corruption in Indonesia - Danny Permana (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Corruption is a serious problem in Indonesia. Therefore, efforts need to be made to eradicate corruption properly. The Corruption Eradication Commission (KPK) plays a pivotal role in combating corruption. This study seeks to examine the methods employed by the KPK in its anti-corruption endeavors. It will utilize a descriptive qualitative methodology, drawing upon a range of prior research findings and literature reviews as its data sources. The results of this research then found that there are various obstacles in fighting corruption. Therefore, there is a need for cooperation between state institutions in eradicating corruption. This can be done through coordination or preparing work protocols. Then, to increase the credibility of state institutions in eradicating corruption, this can be done by increasing transparency and budget management, strengthening accountability and independence, and increasing public participation in eradicating corruption.